THE ROLE OF GREEN INTELLECTUAL CAPITAL AND EMPLOYEE INNOVATIVENESS IN ENHANCING JOB AND FINANCIAL PERFORMANCE: INSIGHTS FROM INDONESIA'S STATE-OWNED ENTERPRISES - Darmansyah, Darmansyah; Bambang Purwoko; Irvandi Gustari; Agung Dinarjito (International Journal of Social Science, 2025)
This study aims to examine the impact of green intellectual capital on job performance and financial performance, with employee innovativeness serving as an intervening variable. Employing a quantitative approach, the research utilizes primary data collected through questionnaires distributed to employees of state-owned enterprises (SOEs) and their subsidiaries in the logistics services sector, ranging from top management to staff levels. The findings reveal that green intellectual capital has a direct and positive influence on employee innovativeness, financial performance, and job performance. However, employee innovativeness does not mediate the relationship between green intellectual capital and either job performance or financial performance. The study underscores the importance of an employee-centric strategy for enhancing workforce performance, innovation, and financial outcomes. Policymakers and corporate leaders are encouraged to prioritize intellectual capital development within their organizations. The results affirm that robust intellectual capital contributes significantly to heightened employee innovativeness, improved job performance, and stronger financial results. Consequently, companies must take proactive steps to cultivate and sustain intellectual capital that drives both organizational and individual success.